2020
DOI: 10.3390/cancers12040925
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Sarcopenia and Skeletal Muscle Loss During Neoadjuvant Chemoradiotherapy in Esophageal Cancer

Abstract: Backgrounds: The relationship between sarcopenia, characterized by loss of muscle mass and strength, and survival outcomes of esophageal cancer is controversial. This study aimed to assess the effect of sarcopenia and skeletal muscle loss on overall survival (OS) and recurrence-free survival (RFS) of esophageal cancer patients. Methods: We retrospectively collected the medical records of 248 male patients diagnosed with squamous cell esophageal cancer and who underwent neoadjuvant chemoradiotherapy (NACRT) fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 57 publications
6
58
1
1
Order By: Relevance
“…This meta-analysis found that sarcopenia following NAT had an adverse impact on long-term survival outcomes of EC patients, which was consistent with other reports ( 9 , 32 , 33 ). However, there was a novel additional suggestion in the study.…”
Section: Discussionsupporting
confidence: 92%
“…This meta-analysis found that sarcopenia following NAT had an adverse impact on long-term survival outcomes of EC patients, which was consistent with other reports ( 9 , 32 , 33 ). However, there was a novel additional suggestion in the study.…”
Section: Discussionsupporting
confidence: 92%
“…Among Chinese individuals aged 50-74, Wu et al (25) reported that a higher UA level was independently related to better HGS. A cross- (29)(30)(31). In this study, however, additional adjustment for hs-CRP did not alter the results showing the association between the serum UA level and HGS; this suggests that inflammation is not the primary mechanism for this association among Chinese adults older than 45.…”
Section: Discussioncontrasting
confidence: 58%
“…A few groups have reported that the loss of skeletal muscle mass and development of sarcopenia during disease course carries prognostic impact on oncologic outcomes, rather than just the presence of sarcopenia at baseline 26,29,30 . Yoon et al recently reported that although the presence of sarcopenia prior to neoadjuvant chemoradiotherapy and surgery was not prognostic, a 10% decrease in SMI during treatment was significantly associated with overall survival 30 .…”
Section: Discussionmentioning
confidence: 99%
“…A few groups have reported that the loss of skeletal muscle mass and development of sarcopenia during disease course carries prognostic impact on oncologic outcomes, rather than just the presence of sarcopenia at baseline 26,29,30 . Yoon et al recently reported that although the presence of sarcopenia prior to neoadjuvant chemoradiotherapy and surgery was not prognostic, a 10% decrease in SMI during treatment was significantly associated with overall survival 30 . Similarly, in the metastatic setting, Sugiyama et al studied 231 patients with metastatic gastric cancer receiving platinum‐based chemotherapy, and found that though pretreatment sarcopenia was not associated with time to treatment failure or overall survival, muscle loss during treatment was associated with inferior survival outcomes 20 .…”
Section: Discussionmentioning
confidence: 99%